Risk factors for medial meniscal pathology on knee MRI in older U.S. adults: A multicenter prospective cohort study - Englund, Martin (Ann Rheum Dis, 2011)
OBJECTIVES: Knee trauma is a known cause of meniscal tear. However, meniscal pathology where the aetiology is often unclear is a frequent finding on knee magnetic resonance imaging (MRI).Our objective was to investigate potential risk factors for medial meniscal lesions or extrusion in middle-aged and elderly persons. METHODS: Prospective cohort study using population-based subjects from Birmingham, Alabama and Iowa City, Iowa, United States (the Multicenter Osteoarthritis Study (MOST)). We studied 644 men and women aged 50 to 79 years with or at high risk of knee osteoarthritis (Kellgren and Lawrence grade 0 to 2) but with normal medial meniscal status at baseline. We scored paired baseline and 30-month 1.0T knee MRIs for meniscal lesions and extrusion (pathology) and evaluated the following systemic, knee-specific, and compartment-specific potential risk factors: age, sex, body mass index, bony enlargement of finger joints, knee trauma, leg-length inequality, and knee alignment. RESULTS: Of 791 knees, 77 (9.7%) had medial meniscal pathology at 30-months follow-up. Sixty-one of these 77 knees (81%) had no report of trauma during follow-up. Including all potential risk factors in the multivariable model, the adjusted odds ratio (OR) for medial meniscal pathology was 4.14 (95% confidence interval 2.06, 8.31) for knee trauma during follow-up, 1.64 (1.00, 2.70) for ≥5 bony enlargements of finger joints (vs. ≤4), and 2.00 (1.18, 3.40) for varus alignment (vs. not varus) at baseline exam. Further, obesity was a risk factor for the development of meniscal extrusion, OR 3.04 (1.04, 8.93) but not for meniscal lesions, OR 1.15 (0.52, 2.54). CONCLUSIONS: Apart from knee trauma, possible generalised osteoarthritis, expressed as multiple bony enlargements of finger joints, varus alignment, and obesity are risk factors for medial meniscal pathology.